Novel SiO2‐Supported Chromium Oxide/Chromocene Dual Site Catalysts for Synthesis of Bimodal UHMWPE/HDPE in Reactor Alloys. Issue 7 (16th March 2020) - Wang, Kai; Jin, Yulong; Liu, Boping; Zhang, Rui; Ren, He; Zhao, Ning; He, Xuelian
Abstract: Polyethylene (PE) with bimodal molecular weight distribution (MWD) has drawn attention from both academia and industry. Bimodal PE combines great processability with outstanding mechanical properties. The single‐reactor technology process through a dual site catalyst system is an optimal strategy considering the economic effect and the manufacturing technique. To satisfy the demand of the dual site catalyst system for producing bimodal PE, novel SiO2 ‐supported chromium oxide/chromocene dual site catalysts for ethylene polymerization are successfully synthesized and systematically investigated. The novel catalysts are prepared by using the residual hydroxyl groups on the surface of SiO2 ‐supported chromium oxide (CrO x ) Phillips catalyst to introduce chromocene. It is found that the novel dual site catalysts combine the advantages of chromocene catalyst (S‐9 catalyst) and Phillips CrO x /SiO2 catalyst. The activities of the dual site catalysts are doubled at least compared to the S‐9 catalyst due to the high activity of the CrO x active center. The products of the dual site catalysts show significantly high molecular weight (MW) with bimodal MWD through ultrahigh molecular weight polyethylene/high‐density polyethylene in reactor alloys. The dual site catalysts show great hydrogen response according to the hydrogen experiment results, which lead to the easy control of MW. Abstract : A novel SiO2 ‐supported chromium oxide (CrO x )/chromocene dual site catalyst for bimodal ultrahigh molecular weight polyethylene (UHMWPE)/high‐density polyethylene (HDPE) is synthesized. The high molecular weight fraction is over 1 × 10 6 g mol −1 and the molecular weight distribution can be controlled by the different loading of active center. The dual site catalyst shows great hydrogen response.